Sistem Pendukung Keputusan Penerimaan Pegawai Baru PT.PLN (Persero) Kantor Pusat dengan Menggunakan Metode Simple Additive Weighting (SAW) - Herlinda De Christin; Yasni Djamain (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2015)
PT PLN (Persero) is the largest state owned companies in Indonesia that handle electricity services throughout Indonesia and is headquartered in Jakarta. To support the progressive growth and build the organizational capability, PT PLN (Persero) in serving the community needed human resources berkualitas.Dalam it is necessary to build a decision support system to assist in the selection and set-based employee PT.PLN (Persero). Wrong a model that can be used for decision support system is a model of Multiple Attribute Decision Making (MADM) with Simple Additive weighting method (SAW). This method was chosen because this method determines the weight values for each attribute, followed by a ranking process that will select the best alternative. Research carried out by finding the weights for each criterion, and then make the ranking process that will determine the optimal alternative is the best applicants. Results of the application decision support system is the best alternative to the election of the applicant is entitled to be an employee because of pass selection in sequence according to the ranking using the programming language PHP.